Electronic Properties of Ag Reconstructions on Si(111): Coulomb Blockade Behavior at Room Temperature. Issue 4 (15th February 2018) - Chandola, Sandhya; McGilp, John; Esser, Norbert
Abstract : The electronic properties and optical response of Si(111)–Ag reconstructions, with distinct interface structures, are studied with scanning tunneling microscopy (STM), reflectance anisotropy spectroscopy (RAS), and infrared spectroscopic ellipsometry (IRSE). The results are compared to previous studies on the Si(111)‐(3 × 1)–Ag surface. Depending on the preparation conditions, STM shows hybrid surfaces comprising (√3 × √3) areas with semiconducting (3 × 1)–Ag regions or metallic Ag islands. RAS of the (√3 × √3)–Ag reconstruction mostly shows a flat response, confirming the isotropic nature of the surface while Ag islands on this surface produce a steep increase in the infrared as well as a strong optical anisotropy at 3.5 eV. Scanning tunneling spectroscopy (STS) of the islands shows a high density of states with almost no structure. STS of Ag nanodots on the (3 × 1)–Ag surface shows distinct Coulomb resonances within the Si bandgap while the Si(111)‐(3 × 1)–Ag surface reveals an expected semiconducting behavior with a band gap and no sign of resonances. Ag islands on the (3 × 1)–Ag surface also show weak Coulombic oscillations indicating that local transport depends on the electronic properties of the interface. Abstract : Ag reconstructions on Si(111) are studied with scanning tunneling microscopy (STM), reflectance anisotropy spectroscopy (RAS) and infrared spectroscopic ellipsometry (IRSE) in order to correlate their morphology with their electronic and optical properties. The growth of the different Ag reconstructions can be controlled precisely with RAS. The evolution of local electronic properties with different Ag nanostructures is investigated and shown to be strongly dependent on the electronic structure of the interface.